PENTINGNYA PERENCANAAN MUTU DALAM PELAYANAN KESEHATAN - Lerina Tampubolon; Nadya Hasnafi Inra; Windy Mayasari; Budi Hartono (LPPM Universitas Abdurrab, 2024)
Health services that care and are centered on the needs, expectations, and values of customers as the starting point for the provision of health services and become requirements that must be met in order to provide satisfaction to the community as users of health services are good and quality health services. Health services not only prioritize patient safety but also must pay attention to the quality or quality of service, so it is necessary to carry out quality planning in carrying out health services. This analysis involved a range of relevant scientific journals on quality planning in healthcare. Data was collected from several articles published in national journals to discuss quality planning in healthcare.